PARENT ROCKS AND SOIL FERTILITY - Migunova, E. S. (Forestry and Forest Melioration, 2018)
The article describes the basic principles of the science of soils as a habitat environment for plants that had emerged at the dawn of civilization, studies soil fertility and classifies soils in texture (particle size). The article also provides insight into direction of the study of soil as a special natural body by structure of the vertical profile, grounded by V. V. Dokuchayev. The necessity of composition and soil structure study on the base of developments of forest typology was grounded, and first of all of the study of the gross amounts of the major bio-elements (phosphorus and potassium) the source of which are the parent rocks. The very significant lack of national soil science is long-term exaggerated value of the morphological structure of the soils, with insufficient attention to their composition due to the original parent rocks and their particle size distribution. The soil structure is formed by moisture regime. Water is the sculptor of the face of the earth, and it defines the formation of different types of soil. Therefore, the genetic type makes it possible to evaluate soil moisture. But the structure of the profile doesn’t have a particular effect on the fertility of the soil, especially longtime plowing largely offsetting. This explains the lack of attention of production organizations to soil science modern developments. The chosen path as a transition into the category of academic science is not the right way. The soil is the main habitat of the plants and the main object of agricultural production. Its basic function is to create the most favorable conditions for plant growth. Therefore, classical soil scientists considered the soils science the central agricultural discipline, the theoretical basis of agriculture. More than 100 years ago, N. M. Sibirtsev proposed to unite genetic soil science that studies the soil as a natural body by the structure of its profile with existing for centuries doctrine about soils as a habitat of plants, assessing them by fertility and classifying them according to particle size, based on the experience of such a study, accumulated by forest typology.